E-learning materials for the Slovene language in elementary schools (6th‒9th grade) - Valh Lopert, Alenka; Koletnik, Mihaela (Revija za elementarno izobraževanje, 2019)
The theoretical part of the paper presents the project Slovenščina na dlani (Slovene in the palm of your hand), which is intended for the establishment of an interactive learning environment for the Slovene language (as mother tongue) in elementary and secondary schools. In this paper we limit the research to elementary school. In the empirical section, we focus on freely available e-learning materials for the Slovene language from the 6th to the 9th grade of elementary school and present the results of an analysis of 10,118 tasks according to their types. The findings indicate an unbalanced representation of different types of tasks, with short answer types in the majority, the task type that is least popular among students. By introducing the most advanced linguistic technology into learning processes, we try to overcome the limitations of existing e-resources for learning the Slovene language.